A Bimetallic Zn/Fe Polyphthalocyanine‐Derived Single‐Atom Fe‐N4 Catalytic Site:A Superior Trifunctional Catalyst for Overall Water Splitting and Zn–Air Batteries. (30th May 2018) - Pan, Yuan; Liu, Shoujie; Sun, Kaian; Chen, Xin; Wang, Bin; Wu, Konglin; Cao, Xing; Cheong, Weng‐Chon; Shen, Rongan; Han, Aijuan; Chen, Zheng; Zheng, Lirong; et al.
Abstract: Developing an efficient single‐atom material (SAM) synthesis and exploring the energy‐related catalytic reaction are important but still challenging. A polymerization–pyrolysis–evaporation (PPE) strategy was developed to synthesize N‐doped porous carbon (NPC) with anchored atomically dispersed Fe‐N4 catalytic sites. This material was derived from predesigned bimetallic Zn/Fe polyphthalocyanine. Experiments and calculations demonstrate the formed Fe‐N4 site exhibits superior trifunctional electrocatalytic performance for oxygen reduction, oxygen evolution, and hydrogen evolution reactions. In overall water splitting and rechargeable Zn–air battery devices containing the Fe‐N4 SAs/NPC catalyst, it exhibits high efficiency and extraordinary stability. This current PPE method is a general strategy for preparing M SAs/NPC (M=Co, Ni, Mn), bringing new perspectives for designing various SAMs for catalytic application. Abstract : Einzeln sind sie stark : Eine Polymerisations‐Pyrolyse‐Abdampfungs(PPE)‐Strategie für die Synthese von N‐dotiertem porösem Kohlenstoff (NPC) mit verankerten atomar dispergierten FeN4 ‐Zentren wurde entwickelt. Das Material ist ein überlegener trifunktioneller Katalysator für die Wasserspaltung und Zn‐Luft‐Batterien. PPE eignet sich allgemein für die Herstellung von M‐Einzelatom/NPC‐Materialien (M=Fe, Co, Ni, Mn).